Caracterização morfométrica de sementes e plântulas e germinação de anadenanthera macrocarpa (benth.) brenan - de Oliveira, Silvia Sanielle Costa [UNESP]; de Araújo Neto, João Correia; Cruz, Sihélio Júlio Silva [UNESP]; Ferreira, Vilma Marques (Universidade Federal de Santa Maria, 2012)
Anadenanthera macrocarpa (Benth.) Brenan is a tree species belonging to the family Leguminosae-Mimosoideae which is popularly known as mimosa-black. It features characteristics of early successional, natural occurrence in Brazil and can form clusters almost homogeneous, with great potential in the recovery of degraded areas. This study was conducted at the Center for Agricultural Sciences, University Federal of Alagoas state, aiming at the physical and morphological characterization of seeds, describing the various stages of post-seminal development, and to evaluate various conditions of temperature and substrate to perform the test germination. The seeds were manually extracted, then homogenized, where two samples of 50 seeds were used to determine the initial moisture. Another sample, consisting of eight repetitions of 100 seeds was used to measure the biometry and the number of seeds per fruit. The morphological characterization and the seeds were immersed in distilled water to allow the cuts to the observed structure in microscopes. In the post-seminal study, it was observed the daily processes of seedling growth in rolled paper filter and constant temperature of 30 °C. To assess the germination behavior, the constant temperatures of 15 °C, 25 °C, 30 °C, 40 °C and 20-30 °C as well as the paper and the sand substrates were tested and it was evaluated the percentage, the rate of germination, the relative frequency distribution, and the tests conducted in a randomized design in factorial 5 x 2 (x substrate temperature) with four replicates of 25 seeds, and the averages compared by Duncan 5 % probability. The fruits of black angico show great variation in the seed number per fruit. The embryonic axis occupies part of the central region of the seed with axial and linear positions. The germination is epigeal and the seedlings are fanerocotylar. The temperature determines the 30 °C and the filter paper substrate provided higher average percentage and germination rate.
Morphometric Characterization Of Seeds And Plantules And Anadenanthera Macrocarpa (Benth.) Brenan Germination
Keywords: Biometrics; Forest species; Mimosa-black; Anadenanthera macrocarpa; Fabaceae; Mimosa; Mimosoideae